Microwave and Millimeter Wave Sensors for Industrial, Scientific and Medical Applications in BiCMOS Technology - Jan Wessel; Klaus Schmalz; Rahul Kumar Yadav; Pouva Soltani Zarrin; Farabi Ibne Jamal; Defu Wang; Gunter Fischer (2020 IEEE International Symposium on Radio-Frequency Integration Technology (RFIT), 2020)
This work gives an overview of integrated microwave to millimeter wave sensors and their applications covering frequencies from 28 GHz to 240 GHz. The designs are capable to address versatile application fields from liquid compound measurements to plaque detection and classification in arteries, glucose detection in continuous glucose monitoring (CGS) systems and virus detection in the context of respiratory diseases. The demonstrated approaches represent powerful and miniaturized solutions for highly sensitive contactless sensing of sample properties. Exploiting millimeter wave frequencies enables highest levels of integration to implement miniaturized sensing solutions including on-chip readout systems.